Answer:
2nd, 3rd and 4th equations are correct.
Step-by-step explanation:
[tex]-4x^2(2x^2+5)=-8x^4-20x^2\\\\[/tex]
is right because each term inside is multiplied by -4x square and we find the answer is right.
[tex]-4b^3(5b^2+3)\\\\\\= -4(5)(b^3)(b^2) =-20b^6-12b^3\\[/tex]
Hence correctly done.
[tex]-5a^4(2a^2+4)= (-5)(2)(a^4)(a^2)+(-5)(4)(a^4\\-10a^6-20a^4\\[/tex]
Correctly done.
[tex]-6^4(4y^2+2)=-24y^8-12y^4\\= -(6)(6)(6)(6) 4y^2 -(6)(6)(6)(6) (2)[/tex]
should be the right answer.
But instead only 6 is multiplied by inner terms. Hence wrong.
I answer is wrong and others are right.